Enduring sex-dependent implications of pubertal stress on the gut-brain axis and mental health - Dworsky-Fried, Michaela; Tchida, Jessica A.; Krnel, Rebecca; Ismail, Nafissa (Frontiers in Behavioral Neuroscience, 2024)
The gut-brain axis (GBA) is a network responsible for the bidirectional communication between the central nervous system and the gastrointestinal tract. This multifaceted system is comprised of a complex microbiota, which may be altered by both intrinsic and extrinsic factors. During critical periods of development, these intrinsic and extrinsic factors can cause long-lasting sex-dependent changes in the GBA, which can affect brain structure and function. However, there is limited understanding of how the GBA is altered by stress and how it may be linked to the onset of mental illness during puberty. This article reviews current literature on the relationships between the GBA, the effects of stress during puberty, and the implications for mental health.